Competency Elements Influencing Personnel Working Performance at Provincial Cultural Office Locating in the Lower Northeastern Region II - Arsasuk, Chalanda; Chotiwanich , Piyakanit; Suntramethakul , Anan (Journal of Management Science Chiangrai Rajabhat University, 2023)
The work aimed to study the competency level, the efficiency level, and the competency factors that influenced the performance efficiency. A questionnaire was administered on 150 individuals. Statistics used in data analysis were frequency, percentage, mean, and standard deviation, Pearson’s co-relation coefficients, and a multiple digression analysis. The study found that the opinion concerning the performance competency was overall at the highest level. The opinion on the efficiency was overall at the highest level. The competency in achievement orientation, good services, expertise accumulation, analysis and vision could influence the performance efficiency at a statistical significance of 0.01. The potential to change could influence the performance efficiency at a statistical significance of 0.05. Both the competency and the potential could predict the performance efficiency by 81% (R2adj=.81)